Genetic Transformation of a C. trachomatis Ocular Isolate With the Functional Tryptophan Synthase Operon Confers an Indole-Rescuable Phenotype - O'Neill, Colette Elizabeth; Skilton, Rachel Jane; Pearson, Sarah Ann; Filardo, Simone; Andersson, Patiyan; Clarke, Ian Nicholas (Frontiers in Cellular and Infection Microbiology, 2018)
Chlamydia trachomatis is the leading cause of preventable blindness and the most common bacterial sexually transmitted infection. Different strains are associated with ocular or urogenital infections, and a proposed mechanism that may explain this tissue tropism is the active tryptophan biosynthesis pathway encoded by the genomic trpRBA operon in urogenital strains. Here we describe genetic complementation studies that are essential to confirm the role of tryptophan synthase in the context of an ocular C. trachomatis genomic background. Ocular strain A2497 was transformed with the (urogenital) pSW2::GFP shuttle vector showing that there is no strain tropism barrier to this plasmid vector; moreover, transformation had no detrimental effect on the growth kinetics of A2497, which is important given the low transformation efficiency of C. trachomatis. A derivative of the pSW2::GFP vector was used to deliver the active tryptophan biosynthesis genes from a urogenital strain of C. trachomatis (Soton D1) to A2497 with the aim of complementing the truncated trpA gene common to most ocular strains. After confirmation of intact TrpA protein expression in the transformed A2497, the resulting transformants were cultivated in tryptophan-depleted medium with and without indole or tryptophan, showing that complementation of the truncated trpA gene by the intact and functional urogenital trpRBA operon was sufficient to bestow an indole rescuable phenotype upon A2497. This study proves that pSW2::GFP derived vectors do not conform to the cross-strain transformation barrier reported for other chlamydia shuttle vectors, suggesting these as a universal vector for transformation of all C. trachomatis strains. This vector promiscuity enabled us to test the indole rescue hypothesis by transforming ocular strain A2497 with the functional urogenital trpRBA operon, which complemented the non-functional tryptophan synthase. These data confirm that the trpRBA operon is necessary and sufficient for chlamydia to survive in tryptophan-limited environments such as the female urogenital tract.